DEVELOPMENT OF BIOLOGY E-BOOK TEACHING MATERIALS BASED ON LOCAL POTENTIAL IN ASAHAN DISTRICT ON ECOSYSTEM MATERIALS FOR CLASS X SMA/MA STUDENTS AT SMA NEGERI 1 PULAU RAKYAT - Ade Safitri; Nirwana Anas; Khairuna (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The learning process will run smoothly and effectively if it is supported by infrastructure. One of the infrastructure that can support the learning process is the availability of teaching materials. One of the teaching materials that can be applied is electronic teaching materials (e-books). The purpose of this study was to determine the development of e-book teaching materials based on local potential in Asahan Regency on ecosystem material for class X students at the senior high school level which is valid, practical, and effective. This research is a research and development model of ADDIE. The research trials were carried out on a large scale. The validity of the E-Book is measured using a validation sheet. The validity of the E-Book material that has been developed is 74% categorized as valid, the validity of the media is 88% categorized as very valid, and language validity of 84% which is categorized as very valid. The practicality of the E-Book was measured using field practitioner validation sheets and student response questionnaires. Based on the validation of field practitioners, the practicality percentage of the E-Book is 96%, which is categorized as very practical, and the student response questionnaire is 94%, which is categorized as very practical. The effectiveness of the E-Book is measured by the normalized gain test. The N-Gain score is 0.7 which is categorized as effective because The effectiveness of the E-Book is measured by the normalized gain test. The N-Gain score is 0.7 which is categorized as effective because The effectiveness of the E-Book is measured by the normalized gain test. The N-Gain score is 0.7 which is categorized as effective becauseN-gain > 0.7.